VALUE ORIENTATIONS OF THE FUTURE TEACHER OF HIGHER EDUCATION INSTITUTION - Sultanova, Leila (Mountain School of Ukrainian Carpaty, 2020)
The article substantiates the urgency of the problem of value orientations of the future teacher of higher education institution. The essence of the concepts of "values" and "value orientations" is defined. Values have been found to form the basis of an individual's value orientations. It is distinguished material, socio-political, spiritual values; positive and negative values; values of personality, social and professional groups, national, universal values in the scientific literature. Among the values of human being and culture, in spite of the great variety only some values appear more frequent, as a rule, basic ones: man, life, good, beauty, truth, freedom, etc. In our publication we place emphasis on the value orientations of the future teacher as one of the components of multicultural competence. This is primarily the value orientations of the individual, which act as social determinants of behavior in a multicultural society. The psychological-pedagogical aspect of value orientations is revealed from two positions: research of value orientations as a component of process of a human development and also as a certain result of personal development. The publication emphasizes that the research provides only the study of the content of the value orientations of the future teacher of higher education institution, but does not exclude the possibility of changes in the system of value orientations of the future teacher under the influence of the process of formation and development of multicultural competence organized by us. The method of determining the level of value orientations is described. For this, it was used Milton Rokeach’s technique «Value Orientation» who distinguishes two classes of values: terminal and instrumental. Conducted the qualitative and quantitative analysis of the future teacher’s system of value orientations before and after the implementation of the four stages of formation of multicultural competence proved the effectiveness of the developed and proposed content of multicultural education.